Positive impacts of Covid-19 pandemic to strengthen National Health Defense - Widyati, Widyati; Widana, I Dewa Ketut Kerta (Technium Social Sciences Journal, 2021)
During the past one and a half year, we all have faced the COVID-19 pandemic. In national defense perspective, COVID-19 Pandemic could be viewed as a non-military threat to national defense. The COVID-19 pandemic is a wake-up call that improves our awareness on the necessity to be fully independent and self-sufficient in health sector. So far, we have been complacent with the ease of importing raw materials for medicines and medical devices. Thus, the advent of the COVID-19 pandemic has made us aware to reduce Indonesia’s high dependence on import of health and medicine goods. Despite of the losses and prolonged sadness brought by the COVID-19 pandemic, there are also positive impacts for this nation as the result of the COVID-19 pandemic. One of the impacts on the National Health System is the strengthening and involvement of all levels of society and the apparatus in dealing with COVID-19 pandemic, which can be seen in the prevention, detection, and orderly response to COVID-19. Adjustment of public health service capacity is also carried out very swiftly to respond the pandemic situation. Another indicator is seen in the financing of medical and healthcare sector that was able to rapidly finding sources of funding for a very sharp increase in public health needs. Meanwhile, Human Resources capacity development appears to be very prominent as seen from the rapid improvement of training and research in medical and healthcare competences. No less important is the pharmaceuticals and medical devices sectors that are more determined to improve their independence and self-sufficiency in terms of drugs and vaccines raw materials. Independent raw materials provision for drugs and vaccines has an important value in the national economy and strengthening national security in the public health sector.